2019
DOI: 10.1007/s00127-019-01803-w
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempt following sickness absence and disability pension due to common mental disorders: a prospective Swedish twin study

Abstract: The aim of this study was to investigate if sickness absence and disability pension (SA/DP) in general and due to specific common mental disorders (CMDs) are associated with subsequent suicide attempt among women and men by taking familial factors (genetics and shared environment) into consideration. Methods This register-based cohort study includes 4871 twin pairs 18-65 years of age discordant for SA/DP due to CMDs 2005-2010. Twins were followed up for suicide attempt from inpatient and specialised outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…The two largest trajectory groups included nearly half of the sample who had received on average a few months/year of SA/DP benefits, and approximately a further third of the sample who had received more than 10 months/year of SA/DP benefits. A prospective twin study observed that twins with MHC who received either SA or DP benefits between 2005 and 2010 had greater risk of self-harm than their adult twins without SA/DP receipt (68). Finally, a Danish retrospective case-control study observed that receipt of SA benefits was a significant risk factor for suicide in men, but not women, but that receipt of a disability pension was not associated with suicide in either men or women.…”
Section: Studies Of Mixed Samplesmentioning
confidence: 99%
“…The two largest trajectory groups included nearly half of the sample who had received on average a few months/year of SA/DP benefits, and approximately a further third of the sample who had received more than 10 months/year of SA/DP benefits. A prospective twin study observed that twins with MHC who received either SA or DP benefits between 2005 and 2010 had greater risk of self-harm than their adult twins without SA/DP receipt (68). Finally, a Danish retrospective case-control study observed that receipt of SA benefits was a significant risk factor for suicide in men, but not women, but that receipt of a disability pension was not associated with suicide in either men or women.…”
Section: Studies Of Mixed Samplesmentioning
confidence: 99%